THE NOMINATION FOR THE MEANS OF WATERWAY TRANSPORTATION IN VIETNAMESE - Thao, Nguyen Van; Thao, Nguyen Thi (International Journal of Psychosocial Rehabilitation, 2020)
In a modern and developed society, with the outstanding development of science and technology, the connection and communication of humans are increasingly expanded. Therefore, new words, word formation and new meanings are continuously and creatively invented to meet people’s demands of exchanging information and developing global transaction. Subsequently, The emerging demand of nominating things, phenomena, activities, nature or expressing emotions, attitudes, human affection are also rapidly and broadly scaled up. Natural languages which develop new words or meanings basically follow certain rules. Of a wide range of rules, universally two semantically- changed methods in all languages in nominating things are: metaphor and metonymy. This article explored and presented the officially specific names of waterway transportation in Vietnamese in terms of language nomination. Based on the statistic data, the research has generalized ten single nominating models and twenty four complex nominating models in an isolating language - Vietnamese.